Flat band potential determination: avoiding the pitfalls. Issue 45 (8th November 2019) - Hankin, Anna; Bedoya-Lora, Franky E.; Alexander, John C.; Regoutz, Anna; Kelsall, Geoff H.
Abstract : Re-examination of methodologies used for flat band potential determination to help avoid misleading results from the Mott–Schottky approximation. Abstract : The flat band potential is one of the key characteristics of photoelectrode performance. However, its determination on nanostructured materials is associated with considerable uncertainty. The complexity, applicability and pitfalls associated with the four most common experimental techniques used for evaluating flat band potentials, are illustrated using nanostructured synthetic hematite (α-Fe2 O3 ) in strongly alkaline solutions as a case study. The motivation for this study was the large variance in flat band potential values reported for synthetic hematite electrodes that could not be justified by differences in experimental conditions, or by differences in their charge carrier densities. We demonstrate through theory and experiments that different flat band potential determination methods can yield widely different results, so could mislead the analysis of the photoelectrode performance. We have examined: (a) application of the Mott–Schottky (MS) equation to the interfacial capacitance, determined by electrochemical impedance spectroscopy as a function of electrode potential and potential perturbation frequency; (b) Gärtner–Butler (GB) analysis of the square of the photocurrent as a function of electrode potential; (c) determination of the potential of transition between cathodic and anodic photocurrents during slow potentiodynamic scans under chopped illumination (CI); (d) open circuit electrode potential (OCP) under high irradiance. Methods GB, CI and OCP were explored in absence and presence of H2 O2 as hole scavenger. The CI method was found to give reproducible and the most accurate results on hematite but our overall conclusion and recommendation is that multiple methods should be employed for verifying a reported flat band potential.